Reconstructing Indonesia’s Trademark Registration System through the Lens of General Principles of Good Governance to Realize Substantive Justice - Masnun, Muh. Ali; Prasetio, Dicky Eko; Awang, Mohd Badrol; Sulistyowati, Eny (Universitas Negeri Semarang, 2024)
The constitutive or first-to-use system in trademark registration in Indonesia actually creates problems, particularly in failing to meet substantive justice aspects in trademark registration. This is because the constitutive or first-to-use system only provides protection for registered trademarks. This research aims to analyze and reconstruct a trademark registration system that accommodates the General Principles of Good Governance (AUPB). This study provides a novel perspective by integrating the General Principles of Good Governance (AUPB) with Indonesia's trademark registration system, offering a unique approach to enhance substantive justice in trademark law. The research highlights the need for reform in the Indonesian trademark registration process, which can guide policymakers and legal practitioners in improving the accuracy and fairness of trademark protection, thereby reducing disputes and enhancing the protection of intellectual property rights. This research is normative legal research using statutory, conceptual, and philosophical approaches. The research results confirm that the